Recent trends in HIV prevalence in a remote setting of southern India: Insights into arranging HIV control policies - Sekar, Ramalingam; Amudhan, Murugesan; Sivashankar, Moorthy; Mythreyee, Manoharan (The Journal of Infection in Developing Countries, 2013)
Introduction: Constant vigilance of the dynamics of HIV prevalence is important in estimating, regulating, and implementing prevention programs. The objective of this study was to investigate the trend in the prevalence of HIV infection over six years among specific demographic groups in the remote district of southern India. Methodology: All high-risk attendees of the Integrated Counseling and Testing Centre, Government Theni Medical College between April 2005 and December 2010 were included in this study. Characteristics including age, sex, place of residence, literacy, and HIV sero-status were collected as per the guidelines of the National AIDS Control Organization. Results: A total of 50,043 data sets were analyzed; 3,282 (6.6%) tested positive for HIV infection. The prevalence of HIV infection among the ≤ 25 age group was significantly lower as compared to the elderly (4.4% vs. 6.9%; odds ratio 0.62; 95% confidence interval 0.55–0.71; p < 0.01). There was a decline in HIV prevalence among both age groups (Ptrend < 0.01 for ≤ 25 year-old; – 82.3% and Ptrend < 0.01 for > 25-year old, – 14.2%), males (Ptrend < 0.01; – 50.9%), the urban population (Ptrend < 0.01; – 45.9%), and illiterates (Ptrend < 0.01; – 68%). The trend of HIV prevalence among females (Ptrend = 0.48; +9.1%), the rural population (Ptrend = 0.95; – 7.1%), and literate population (Ptrend = 0.44; +28%) was statistically insignificant. Conclusion: HIV prevalence is stable in the female population, while it is decreasing in male population, indicating that current interventions must be strengthened to reduce HIV prevalence among females.